Architecture, Modernity, Modernization : Inaugural Lecture delivered on Thursday 21 May 2014 - Jean-Louis Cohen (Collège de France, 2020)
The history of architecture constantly combines two perspectives: one is panoramic and turned towards urban ensembles so as to reveal social or technical policies, while the other looks in close shot at buildings, their interior, and their reflection of the ideals and engagement of their creators and occupants. By articulating the thoughts of twentieth-century theoreticians, philosophers, writers and architects (such as Mies van der Rohe, Wright, or Le Corbusier), Jean-Louis Cohen offers a new approach to architecture as a subject of inquiry and as a practice - one that is rooted in cultural history and in its human dimension.